Interactions Between Trivalent Elements Enable Ultrastable LDH Cathode for High-Performance Zinc Battery - Junhua Zeng; Jinlei Gao; Wenyao Lu; Jiashuo Feng; Ting Deng (Batteries)
Layered double hydroxides (LDHs) are one class of two-dimensional materials, with tunable chemical composition and large interlayer spacing, that is a potential cathode material candidate for aqueous zinc-ion batteries (AZIBs). Nevertheless, the low conductivity and fragile structure of LDH have impeded their practical application in AZIBs. Herein, a ternary CoMnAl LDH is synthesized via the facile coprecipitation method as the cathode material for AZIB. The interaction between trivalent Al3+ and Mn3+ not only lowers the redox energy barrier but also enhances the electronic structure, as proved by EIS analysis and DFT simulation. As a result, the synthesized CoMnAl LDH displays a high specific capacity of 238.9 mAh g−1 at 0.5 A g−1, an outstanding rate performance (138.8 mAh g−1 at 5 A g−1), and a stable cyclability (92% capacity retention after 2000 cycles).